MEMBINCANG QIYAS SEBAGAI METODE PENETAPAN HUKUM ISLAM - Farid Naya (TAHKIM, 2017)
Qiyas is among the methods for implementing Islamic law. In principle qiyas equate something with something else, meaning equate a pre-existing legal provisions to something that is already in its legal set to something already established legal, because there illat similarities between the two. Qiyas has an important role in this regard Islamic law as the first, Islamic law has been described and set laws in the Qur'an and Hadith are very limited in number and his explanations. Secondly, a new issue arises that there is no legal firmness in the Qur'an and the hadith the prophet is very diverse and complex and constantly in need of certainty. Thus, through the method of qiyas this is all legal issues have not firmness and legal certainty can be resolved properly and correctly. Keywords: qiyas, islamic law